Innovative Strategy for Digital Business Development Based on Object-Oriented Programming to Improve System Efficiency and Scalability - Sihotang, Widodo; Ilmi, Haifah; Syahfitri, Ririn; Zunnurain, Rais Affaruq (Jurnal Transformasi Digital dalam Ekonomi, Bisnis, dan Manajemen, 2025)
Digital transformation has become a major driver in the development of business models in the modern era, demanding efficiency and sustainability in the management of information technology systems. This research aims to examine the role of Object-Oriented Programming (OOP) as a strategic approach in the development of efficient and sustainable digital businesses. Using a library research method and a descriptive qualitative approach and metaanalysis, data was collected from reputable scientific journals, academic books, and other reliable sources. The findings show that OOP principles such as encapsulation, inheritance, polymorphism, and abstraction contribute significantly to the flexibility, scalability, and sustainability of software systems. Case studies of OOP implementations in global digital businesses also corroborate that this paradigm supports operational efficiency and continuous innovation. However, challenges such as design complexity and limited human resources are still obstacles that require strategic solutions, including technical training and careful software architecture planning. This research recommends the integration of OOP in the long-term planning of digital businesses and the need for further empirical studies to quantitatively measure its impact. The implications of these findings are important for developers, academics, and business people who want to build adaptive, efficient, and sustainable digital systems amid technological disruption.